Review of the genera Orionis Shaw and Stenothremma Shaw (Braconidae) from India, with description of three new species - Gupta, Ankita; van Achterberg, Cornelis; Pattar, Rohit; Kumar, H.M. Hemanth; Sushil, S.N. (European Journal of Taxonomy, 2024)
The Indian species of the genera Orionis Shaw and Stenothremma Shaw (Braconidae, Euphorinae) are reviewed. Both genera are reported for the first time from India. Three new species, Orionis shillongensis Gupta, van Achterberg & Pattar sp. nov. from north-eastern India (Meghalaya), O. femorator Gupta, van Achterberg & Pattar sp. nov. from southern India (Karnataka and Tamil Nadu) and Stenothremma flavator Gupta & van Achterberg sp. nov. from southern India (Karnataka) are illustrated and described. A key to the Old World species of Orionis Shaw is provided.